A network analysis on the relationship between depression symptoms and loneliness in elderly Peruvians - Caycho-Rodríguez, Tomás (2025)
Loneliness and depression are the most prevalent mental health issues among older adults, and their relationship has been documented in studies using reflective psychopathological models based on the total scores. However, mental health problems should be investigated at the level of individual symptoms in order to develop intervention strategies aimed at mitigating the adverse impact of both variables. The goal was to examine the extent to which symptoms of loneliness relate to symptoms of depression in elderly Peruvians using the network method in 328 Peruvian adults with an average age of 68.44 years (SD = 7.64). The participants were selected through non-probability convenience sampling, which may limit the generalizability of the results. The Patient Health Questionnaire-2 (PHQ-2) and three-item UCLA Loneliness Scale were used in this study. Network analysis was used to identify central and bridging symptoms within the network of loneliness and depressive symptoms. Furthermore, the invariance in symptom networks between men and women was estimated. The results indicated that ‘feeling excluded’ was the most central symptom. Furthermore, the symptoms ‘feeling excluded’ and ‘anhedonia’ have the strongest relationship and can be considered as bridge symptoms between loneliness and depressive disorders. Symptom networks were invariant between men and women (M =.26; p =.42; S =.09; p =.38). In conclusion, the network structure provides valuable insights into the relationship between the symptoms of loneliness and depression in older Peruvian adults. The results suggest that the symptoms ‘feeling excluded’ and ‘anhedonia’ could serve as potential targets for psychological interventions aimed at efficiently reducing loneliness and depression.